2002
DOI: 10.4049/jimmunol.168.8.3974
|View full text |Cite
|
Sign up to set email alerts
|

Role of NADPH Oxidase in the Mechanism of Lung Neutrophil Sequestration and Microvessel Injury Induced by Gram-Negative Sepsis: Studies in p47phox−/− and gp91phox−/− Mice

Abstract: We addressed the role of O⨪2 generated by the NADPH oxidase complex in the mechanism of polymorphonuclear leukocyte (PMN) accumulation and transalveolar migration and lung microvascular injury. Studies were made in mice lacking the p47phox and gp91phox subunits of NADPH oxidase (p47phox−/− and gp91phox−/−) in which PMN are incapable of the respiratory burst. The mice were challenged i.p. with live Escherichia coli to induce sepsis. We observed time-dependent increases in PMN sequestration and migration from 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
145
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(160 citation statements)
references
References 50 publications
11
145
2
2
Order By: Relevance
“…Catalasenegative organisms lack this ability and, in theory, the H 2 O 2 produced by catalase-negative organisms can substitute for defective phagocyte production of ROS. Nevertheless, gp91 phox2/-mice have been shown also to have defective pulmonary killing of catalase-negative organisms, including Escherichia coli, Pseudomonas aeruginosa, and Mycobacterium tuberculosis, in vivo (24)(25)(26), and thus our finding of no defect in pneumococcal killing in gp91 phox2/-mice was unexpected. In keeping with our findings, infection with the pneumococcus, a catalase-negative organism, is rare in CGD (27).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Catalasenegative organisms lack this ability and, in theory, the H 2 O 2 produced by catalase-negative organisms can substitute for defective phagocyte production of ROS. Nevertheless, gp91 phox2/-mice have been shown also to have defective pulmonary killing of catalase-negative organisms, including Escherichia coli, Pseudomonas aeruginosa, and Mycobacterium tuberculosis, in vivo (24)(25)(26), and thus our finding of no defect in pneumococcal killing in gp91 phox2/-mice was unexpected. In keeping with our findings, infection with the pneumococcus, a catalase-negative organism, is rare in CGD (27).…”
Section: Discussionmentioning
confidence: 71%
“…However, understanding these compensatory changes can be informative and it is possible that other approaches, such as the use of small molecular inhibitors, may also trigger these changes. In addition, the finding of greater neutrophil numbers in response to infection is not unique to our model of CGD, whereas the improved bacterial clearance, to our knowledge, is unique (24,25).…”
Section: Discussionmentioning
confidence: 87%
“…Besides triggering cytoskeleton rearrangements, cell polarization, and cell migration, fMLP activates other neutrophil-specific responses including integrin-binding capacity, degranulation, and respiratory burst. These responses are directly or indirectly related to PMN recruitment in the inflammatory site because they mediate integrindependent leukocyte arrest to the inflamed endothelium and transendothelial migration, but also, via the release of granule constituents or reactive oxygen products, endothelial activation, and vascular permeability (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…This study, together with previous findings implicating Src family kinases in degranulation (18,21,23), identifies other possible steps regulating neutrophil recruitment that may depend on Src family kinases. In fact, release of reactive oxygen intermediates or granule constituents may regulate expression of counterreceptors for leukocyte integrins by the vascular endothelium or tightness of the endothelial cell layer (59,60). Therefore, defective release of reactive oxygen molecules in response to chemoattractants may result in reduced activation of endothelial cells and the consequent recruitment of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic mutations in NOX2 (gp91phox), p47phox, p67phox and p22phox are known to be responsible for development of CGD, but minimal evidence exists for associations of these polymorphisms with other diseases, and a recent analysis failed to show an association of polymorphisms within gp91phox, p47phox, p67phox or p22phox with infectious or non-infectious lung diseases, such as tuberculosis or sarcoidosis (199). Attempts to implicate NOX2 or p47phox in models of lung inflammation and injury, using gp91phox−/− or p47phox−/− mice, demonstrated that genetic NADPH oxidase deficiency was in many cases associated with enhanced inflammation and injury (200)(201)(202)(203), implicating that NOX2 also has beneficial functions in regulating inflammatoryimmune responses. For example, infection of gp91phox−/− mice with the yeast C. neoformans or with influenza virus was in either case found to result in increased Th1-skewed inflammation and granuloma formation, compared to their wild-type counterparts, which led to increased influenza clearance and protection against C. neoformans infection (204,205).…”
Section: Nox2mentioning
confidence: 99%